SEMI-QUANTITATIVE PRECIPITATION FORECASTS FOR RIVER PUN PUN BY SYNOPTIC ANALOGUE METHOD - SINGH, K.M.; PRASAD , M. C.; PRASAD, G. (MAUSAM, 1995)
An attempt has been made to issue semi-quantitative precipitation forecasts for river Pun Pun by synoptic analogue method. Based upon twelve years data (1982-93) the study reveals that it is possible to issue semi-quantitative precipitation forecasts with confidence. The severe floods in the river Pun Pun pose problems to Patna town due to blocking effect of Ganga.